Efektivitas Mobile Health â€œNifas Sehatâ€ terhadap Selfcare Agency pada Ibu Nifas Primigravida - Ariani, Antri; Mulyani, Yanyan; Oktafiani, Hani (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The World Health Organization (WHO) reported that in 2019, there were 303,000 maternal deaths worldwide, with 99% of them occurring in developing countries. According to the Ministry of Health, the maternal mortality rate in Indonesia was 305 per 100,000 live births in 2012-2015, dropping to 240 per 100,000 live births in 2019. However, this figure is still high compared to developed countries which have a maternal mortality rate of 14 per 100,000 live births.The postpartum period is a critical period for mothers, where 60% of maternal deaths occur after delivery and 50% of these deaths occur in the first 24 hours of the postpartum period. Complications during the postpartum period occur in 73% of cases, but not all of them result in maternal death. Primigravida is a term used to describe a woman who is pregnant for the first time. According to WHO data, the maternal mortality rate for primigravida women is higher than for multigravida women. The most common causes of maternal death in Indonesia are bleeding, hypertension during pregnancy, and infection. The Ministry of Health is working to improve the health service system to reduce maternal and infant mortality rates, including during the Covid-19 pandemic. The aim of this study was to measure the level of self-care agency in primigravida postpartum mothers before and after using mobile health "Sehat Postpartum".